Effect of recent flood on ichthyoplankton and juvenile fish assemblage changes in Kuantan River revealed through DNA barcoding - John, Akbar; Rahman, Mohammad Mustafizur (Universiti Teknologi Malaysia (UTM), 2018)
Identifying early life stages of fishes to the species level is one of the challenging task for the taxonomist as the information on key morphological characters are overlapping between genetically closer individuals. Universal DNA barcode (cytochrome oxidase C subunit 1) gene sequence helped tremendously in species level identification of early life stages of fishes. This study was aimed to address the effect of recent monsoon on assemblage changes in Ichthyoplankton and juvenile fishes of Kuantan river, Whereby, the samples were identified to the species level using COX1 gene sequencing. Samples were collected using modified bubu light trap net between April 2015 and December 2015 in Kuantan river and its all tributaries. Fish larvae/juvenile size ranged from 3mm to 100mm, with most abundant individual belong to size class <10mm. A total of 28 species belong to 15 families were successfully identified to the species level from the total of 58 barcodes generated from 372 larval/juvenile samples collected. Unlike the previous study, significant shift in species assemblage has been recorded in this study. Statistical analysis showed significant effect of salinity and suspended particulate on the species distribution and abundance. The dominant fishes belong to the cyprinidae family followed by toxotidae, ambasidae and eleotridae compared to the previous study (Ariidae, Lactaridae and Lutjanidae). It could be concluded that the recent flood (mid-December 2014 to January 2015) in east peninsular Malaysia will have greater positive impact on Kuantan river fish diversity in near future.